Demographic and Psychological Factors Associated with Feelings of Antibiotic Entitlement in New Zealand - Carol H. J. Lee; Pauline Norris; Isabelle M. Duck; Chris G. Sibley (MDPI AG, 2018)
Patients’ expectations of being prescribed antibiotics can have an important influence on inappropriate prescribing. Therefore, it is important to understand the drivers of patients’ antibiotic expectations. The 2015/16 New Zealand Attitudes and Values Study measured sense of entitlement to antibiotics in a nationally representative sample of New Zealanders (n = 13,484). Participants were asked to rate their agreement with the statement “If I go to my doctor/GP with a minor illness (e.g., sore throat, cough, runny nose, etc.), I think that I should be prescribed antibiotics by default.” Eighty percent of participants showed low feelings of antibiotic entitlement, while 18.5% exhibited moderate and 3.7% high feelings of entitlement. People of ethnic minority, lower socio-economic status, and with diabetes expressed higher expectations of being prescribed antibiotics. This may be partially based on a higher risk of rheumatic fever or other complications. Men, religious people, those with lower educational attainment and self-rated health, but greater psychological distress and feelings of control over their health exhibited higher feelings of antibiotic entitlement. Those high on Extraversion, Conscientiousness, and Narcissism, but low on Agreeableness and Openness, also showed greater feelings of entitlement. Our findings help identify key characteristics of those more likely to express inappropriate expectations of antibiotic prescription.